What happens when separate and unequal school districts merge? - Robert Aue; Thilo Klein; Josué Ortega (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We study the welfare effects of school district consolidation, i.e. the integration of disjoint school districts into a centralised clearinghouse. We show theoretically that, in the worst-case scenario, district consolidation may unambiguously reduce students' welfare, even if the student-optimal stable matching is consistently chosen. However, on average all students experience expected welfare gains from district consolidation, particularly those who belong to smaller and over-demanded districts. Using data from the Hungarian secondary school assignment mechanism, we compute the actual welfare gains from district consolidation in Budapest and compare these to our theoretical predictions. We empirically document substantial welfare gains from district consolidation for students, equivalent to attending a school five kilometres closer to the students' home addresses. As an important building block of our empirical strategy, we describe a method to consistently estimate students' preferences over schools and vice versa that does not fully assume that students report their preferences truthfully in the student-proposing deferred acceptance algorithm.
Keywords: C78; I21; 330; school district consolidation; integration of matching markets; preference estimation without truth-telling